Australian Indigenous Art : Local Dreamings, Global Consumption (Autohtona Australijska Umetnost : Lokalno Sanjarenje, Globalna Potra\vznja) - Ryan, M.; Keane, Michael; Cunningham, S. (Economy Group and The Australian Embassy Belgrade, 2013)
Indigenous Australian visual art is an outstanding case of the dynamics of globalization and its intersection with the hyper-local wellsprings of cultural expression, and of the strengths and weaknesses of state, philanthropic and commercial backing for cultural production and dissemination. The chapter traces the development of the international profile of Indigenous ‘dot’ art – a traditional symbolic art form from the Western Desert – as ‘high-end’ visual art, and its positioning within elite markets and finance supported by key international brokers, collectors and philanthropists.